A graphing calculator is recommended. Let \( f(x)=3 e^{x} \cos (x) \) (a) Find \( f^{\prime}(x) \) and \( f^{\prime \prime}(x) \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
To find the first and second derivatives of \( f(x) = 3 e^{x} \cos(x) \), we can use the product rule and the chain rule. 1. **First Derivative \( f^{\prime}(x) \)**: Let \( u(x) = 3 e^x \) and \( v(x) = \cos(x) \). Then \( u'(x) = 3 e^x \) and \( v'(x) = -\sin(x) \). According to the product rule, \( f^{\prime}(x) = u' v + u v' \): \[ f^{\prime}(x) = (3 e^x)(\cos x) + (3 e^x)(-\sin x) = 3 e^x (\cos x - \sin x) \] 2. **Second Derivative \( f^{\prime \prime}(x) \)**: Now, we differentiate the first derivative. Using the product rule again: Let \( A(x) = 3 e^x \) and \( B(x) = \cos x - \sin x \). Then \( A'(x) = 3 e^x \) and \( B'(x) = -\sin x - \cos x \). Now, applying the product rule: \[ f^{\prime \prime}(x) = A'B + AB' = (3 e^x)(\cos x - \sin x) + (3 e^x)(-\sin x - \cos x) = 3 e^x[( \cos x - \sin x) + (-\sin x - \cos x)] = 3 e^x(-2\sin x) \] Thus, the first derivative is: \[ f^{\prime}(x) = 3 e^x (\cos x - \sin x) \] and the second derivative is: \[ f^{\prime \prime}(x) = -6 e^x \sin x \]